Cancer‐generated lactic acid: a regulatory, immunosuppressive metabolite?. Issue 4 (9th July 2013) - Choi, Stephen Yiu Chuen; Collins, Colin C; Gout, Peter W; Wang, Yuzhuo
Abstract The common preference of cancers for lactic acid‐generating metabolic energy pathways has led to proposals that their reprogrammed metabolism confers growth advantages such as decreased susceptibility to hypoxic stress. Recent observations, however, suggest that it generates a novel way for cancer survival. There is increasing evidence that cancers can escape immune destruction by suppressing the anti‐cancer immune response through maintaining a relatively low pH in their micro‐environment. Tumours achieve this by regulating lactic acid secretion via modification of glucose/glutamine metabolisms. We propose that the maintenance by cancers of a relatively low pH in their micro‐environment, via regulation of their lactic acid secretion through selective modification of their energy metabolism, is another major mechanism by which cancers can suppress the anti‐cancer immune response. Cancer‐generated lactic acid could thus be viewed as a critical, immunosuppressive metabolite in the tumour micro-environment rather than a 'waste product'. This paradigm shift can have major impact on therapeutic strategy development. Copyright © 2013 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.